2001
DOI: 10.1038/sj.sc.3101167
|View full text |Cite
|
Sign up to set email alerts
|

Functional community ambulation requirements in incomplete spinal cord injured subjects

Abstract: Study design: A group of people with incomplete spinal cord injuries (SCI) were evaluated and compared with able-bodied individuals during several walking conditions. Objectives: To evaluate the functional community ambulation and estimated energy expenditure in persons with incomplete SCI and able-bodied individuals. Methods: A list of criteria was used to evaluate functional community ambulation among participants. Physiological variables, such as the heart rate, oxygen uptake and the lactate concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 19 publications
1
79
1
1
Order By: Relevance
“…It is worth noting that a significant number of subjects with a maximal score on the Berg scale or the WISCI had a walking speed below normal or functional value. 22,23 Thus, the maximal score on these two instruments is not necessarily indicative of the normal walking function. A timed or measured walking evaluation, such as the 10MWT, would therefore be a useful adjunct to these evaluations to further characterize higher functioning individuals.…”
Section: Assessment Of Standing Balance For Sci J-f Lemay and S Nadeaumentioning
confidence: 99%
“…It is worth noting that a significant number of subjects with a maximal score on the Berg scale or the WISCI had a walking speed below normal or functional value. 22,23 Thus, the maximal score on these two instruments is not necessarily indicative of the normal walking function. A timed or measured walking evaluation, such as the 10MWT, would therefore be a useful adjunct to these evaluations to further characterize higher functioning individuals.…”
Section: Assessment Of Standing Balance For Sci J-f Lemay and S Nadeaumentioning
confidence: 99%
“…13,14 This group of patients often presents with impairments ranging from minimal sensory and motor loss below the level of lesion to complete motor loss with sacral sparing only. 15 Skeletal muscle adaptations after acute incomplete SCI are not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 This could be explained by the different diagnosis and patient selection, as well as the much smaller study populations than in this study: 48 cerebral stroke patients and 32 AIS D SCI patients. The preferred walking speed of the healthy population is 1.20 to 1.31 m/s, 16 which is about twice as fast as the cutoff walking speed determined in this study. The patients in this study who walk without any walking aids had a mean walking speed of 1.48 m/s, which is similar to the preferred walking speed of the healthy population.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, it has been suggested that a walking speed of 1.20 to 1.31 m/s is required for independent ambulation in the community, since it is similar to the preferred walking speed of nonimpaired people. 16 SCI patients with limited lower extremity muscle power who are unable to bear their body weight (eg, AIS [American Spinal Injury Association Impairment Scale] A, B, and C SCI) can still walk using an exoskeleton. An exoskeleton is an orthosis with electromotors at the hip and knee joints, rechargeable batteries, and a computer-based control system.…”
Section: Introductionmentioning
confidence: 99%